META-ANALYSIS OF MIND MAPPING IN VOCABULARY LEARNING OF THE PAST DECADE - Winda Sari; Ilham Ilham; Hijril Ismail; Humaira Humaira; Rima Rahmaniah; Irwandi Irwandi (University of Kuningan, 2023)
The type of research used is meta-analysis research aimed at determining the level of effectiveness or quality of mind mapping in vocabulary learning, including at elementary, middle, high school, and college levels. This quality was examined using several previous research results that collected data with inclusion and exclusion conditions from the Google Scholar, DOAJ, and Scopus databases. The search results found up to 51 dates that met the requirements with the number of students (N), F-counts, t-counts, and r-counts. The results of data analysis obtained by the simulation software JASP showed that the impact on learning media vocabulary based on mind mapping is 73% significant, which included the High category. The moderator variable is the lowest level of education, the high impact of using mind mapping, namely the college level, with an estimate of the effect of 0.569, Based on the number of participants, the application of mind mapping has more influence on participants totaling more than 30 students with an estimate of 0.928 (strong category), while the lowest effect is seen from the number of participants who collected more than 91 students with an estimate of 0.529, meaning that this mind mapping learning model is most appropriate to be applied in high school rows with more than 30 participants in order to maximize student learning outcomes.